Magnetic resonance urography in duplex kidney with ectopic ureteral insertion - Conjeevaram Rajendrarao Thambidorai; Zulfiqar Anuar (Wolters Kluwer Medknow Publications, 2011)
This is a report on the use of magnetic resonance urography (MRU) in a 6-year-old girl who presented with urinary incontinence. She had a left duplex kidney with poorly functioning upper moiety and ectopic insertion of the dilated upper pole ureter. MRU has been shown to be superior to conventional imaging techniques in delineating poorly functioning moieties of duplex kidneys and ectopic ureters.